GAGURITAN DANGHYANG NIRARTHA KAJIAN NILAI-NILAI SOSIAL-RELIGIUS - Ni Nyoman Kertiasih (Universitas Warmadewa, 2021)
This paper is a study about a literary work, Gaguritan Danghyang Nirartha (GDN), which is taken up from the book Sedjarah Danghyang Nirartha, wrote by Ida Bagus Putu Bek, printed by Pustaka Balimas (1961). This literary work is written in Balinese, in the form of a song (tembang). GDN told about a historical event of Danghyang Nirartha, who well known as a spiritualist in the Hindu religion. In about of his historical event, it told particularly when he was in Bali, where he had well come in the society. He met with Bendesa Mas in Mas village, and there Danghyang Nirartha purified two persons who became bhagawan (holy man), namely: I Bendesa Mas and Kiyayi Dauh Panulisan. And then he invited by the King to come to Gelgel palace, met the King of Gelgel. There Danghyang Nirartha got big honor from the King and appointed as a priest (bhagawanta) of the Kingdom. The purpose of this paper is to examine the literary work GDN, by looking at values: social-religious values, sociological, and moral values. In the sense of the theoretical approach, the content analysis model is used in this study, which is taken from Suwardi Endraswara (2003). As a result, in this study can be found some values: Hindu religion values, sociological values, and moral etic values, which are very useful to become better in the living of the society. Keywords: Bendesa Mas; Danghyang Nirartha; Waturenggong